A Preliminary Benthic Macroinvertebrate Survey of The Gunung Belumut Recreational Forest, Kluang, Johor - Aweng Eh Rak; Ismid Said; Maketab Mohamed; Ahmad Abas; Chow, V.K.K (2010)
The macro invertebrate community structure was surveyed at Sungai Dengar sub-catchment located in Gunung Berlumut Recreational Forest in Kluang, Johor from 08 to 11 August 2009 by using surber net. River water quality and river features were also identified. The surfaced water dissolved oxygencontent ranged from 7.11 mg/1 to 8.06 mg/1. The maximum value of 8.06 dissolved oxygen content was recorded at site A (Gunung Berlumut ). The pH values ranged from 7.47 to 7.89. the maximum value was recorded at site B (pristine area) while the minimum value was recorded at site A (Gunung Berlumut). The surface temperature varied between 23.6 oC to 25.3 oC. the maximum temperature was observed at site C and the minimum temperature was noted at site A. The conductivity values varied between 27.4 uS/cm to 29.10 uS/cm. the maximum conductivity was recorded at site C and the minimum turbidity values recorded at site B and the minimum values were recorded at site A. the dissolved oxygen, pH, temperature and conductivity values did not show any distinct variation between stations except turbidity. Based on the result, it shows that Diptera particularly Chironomidae were abundant at pristine-pritine site which is the most up-stream (undisturbed) located on the Gunung Berlumut and also at the station B2 which was pristine station located at the foot of Gunung Berlumut but nevertheless the numbers of individual taxa are much higher at polluted sited (C1 & C2). Pristine-pristine also recorded an abundant of Mollusca particularly from the family of Atyiedae and Palaemonidae. The results obtained also shoes an abundant of the genus of Pseudiron,Potamanthus and Ephemerella from ephemeroptera order at the polluted sites (C1 & C2), besides Chironomidae, odonata, trichoptera Coleopatra and Mesogastropoda were the orders least found at all the sampling stations. Only five (5) individual Odonata, twelve (12) individual Trichoptera, ten (10) individual Coleopatra and one (1) individual Mesogastropoda were collected. On the other hand, only one (1) family (Perlidae) and one (1) genus (Neoperla) were found from the Plecoptera order at all the sampling stations and one (1) family (Lymnaeidae) from the genus Lymnaea was collected atstation B1. Based on the above results, it could be implied that, macro invertebrate community structure was not dependent solely on water quality of the river but it was also dependent on other factors such as habitat characteristics, river morphology, river riparian, canopy cover, etc., especially river substrate compositions.